Bystander CPR occurrences in out of hospital cardiac arrest between sexes. (September 2021) - Souers, Amy; Zuver, Christian; Rodriguez, Alexa; Van Dillen, Christine; Hunter, Christopher; Papa, Linda
Abstract: Background: Bystander CPR (B-CPR) is known to be a critical action in treating out-of-hospital cardiac arrest (OHCA). Immediate CPR may double a patient's chance of survival. Only 40% of OHCA patients receive B-CPR (Cardiac Arrest Registry to Enhance Survival 1 ). Civilians may be more comfortable performing CPR on male than female victims based on stereotyped training and the culture of cardiac disease treatment. Objective: We hypothesize that of OHCA patients receiving B-CPR, there is a gender disparity favoring males. Methods: This is a retrospective analysis of the National Emergency Medical Services Information System (NEMSIS) dataset. 149, 734 cases were included in this analysis. Primary outcome was frequency of B-CPR between genders. Secondary analysis included gender disparity in AED pad placement, and subsets divided by type of bystander. Results: Among 149, 734 OHCA, 78, 738 received B-CPR. 28, 485 of 55, 215 females (51.59%) received B-CPR, compared to 50, 253 of 94, 519 males (53.17%, p < 0.001). Of OHCA with bystander AED pad placement, 22.9% of females had AED pads applied, compared to 24.6% of males (p < 0.001). In OHCA witnessed by family member, 57.80% of females versus 61.70% of males received B-CPR (p < 0.001). In OHCA witnessed by layperson, 62.50% of females versus 69.00% of males received B-CPR (p < 0.001). Conclusion: There was a significantly lower rate of B-CPR in women experiencing OCHA in the population sample analyzed. Continued education and research are needed on the topic to address gender-specific differences in OHCA.